Pengembangan Buku Teks Berbasis Etnomatematika Masjid Agung Jawa Tengah untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa - Shabrina Putti Nilasari; Dyana Wijayanti; Hevy Risqi Maharani (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2023)
This research was conducted to develop a textbook based on ethnomathematics at the Great Mosque of Central Java that is valid, practical and effective in improving students' ability to think creatively on quadrilateral material. The method used is Research and Development (R&D) with the ADDIE (Analyze, Design, Development, Implementation and Evaluation) model. The subjects of this research were 24 students in class VII A at one of the Semarang City Middle Schools. Data collection methods were obtained from media expert and material expert validation sheets, teacher and student response questionnaires, as well as pre-test questions and post-test questions. The product produced is a Textbook Based on Ethnomathematics at the Great Mosque of Central Java which was declared valid based on the validation results of material experts and media experts, the product was declared practical based on the results of teacher and student response questionnaires, and the product was declared effective in improving students' ability to think creatively based on the results of the pre-test scores. and student post test scores. It is hoped that this research will attract the interest of future researchers to develop other ethnomathematics-based textbooks with valid, practical and effective categories for improving the quality of learning.